MRI monitoring of focused ultrasound sonications near metallic hardware. Issue 1 (7th December 2017) - Weber, Hans; Ghanouni, Pejman; Pascal‐Tenorio, Aurea; Pauly, Kim Butts; Hargreaves, Brian A.
Abstract : Purpose: To explore the temperature‐induced signal change in two‐dimensional multi‐spectral imaging (2DMSI) for fast thermometry near metallic hardware to enable MR‐guided focused ultrasound surgery (MRgFUS) in patients with implanted metallic hardware. Method: 2DMSI was optimized for temperature sensitivity and applied to monitor focus ultrasound surgery (FUS) sonications near metallic hardware in phantoms and ex vivo porcine muscle tissue. Further, we evaluated its temperature sensitivity for in vivo muscle in patients without metallic hardware. In addition, we performed a comparison of temperature sensitivity between 2DMSI and conventional proton‐resonance‐frequency‐shift (PRFS) thermometry at different distances from metal devices and different signal‐to‐noise ratios (SNR). Results: 2DMSI thermometry enabled visualization of short ultrasound sonications near metallic hardware. Calibration using in vivo muscle yielded a constant temperature sensitivity for temperatures below 43 °C. For an off‐resonance coverage of ± 6 kHz, we achieved a temperature sensitivity of 1.45%/K, resulting in a minimum detectable temperature change of ∼2.5 K for an SNR of 100 with a temporal resolution of 6 s per frame. Conclusion: The proposed 2DMSI thermometry has the potential to allow MR‐guided FUS treatments of patients with metallic hardware and therefore expand its reach to a larger patient population. Magn Reson Med 80:259–271, 2018. © 2017 International Society for Magnetic Resonance in Medicine.